Carolyn B. Dexter Award Finalists - Christodoulides, Paul (My University, 2026)
https://aom.org/membership/awards-and-recognition/annual-meeting-program-awards/2019-annual-meeting-program-awards "The Impact of Proximity on Consumer Fair Trade Engagement and Buying Behavior" Submitted to Organizations and the Natural Environment Authors: Paul Christodoulides, Alvina Gillani, Smirti Kutaula, Leonidas Leonidou
Keywords: Sciences